Kajian Antagonisme Hara K, Ca Dan Mg pada Tanah Inceptisol yang Diaplikasi Pupuk Kandang, Dolomit dan Pupuk KCl terhadap Pertumbuhan Jagung Manis (Zea mays saccharata L.) - Irwan Agusnu Putra; Hamidah Hanum (Elkawnie, 2018)
Antagonism nutrient study for K, Ca and Mg in the Inceptisol soil that applied manure, dolomite and fertilizers KCl to the growth of sweet corn (Zea mays saccharata L.). The purpose of this research is to study the interaction between potassium fertilizer, dolomite and chicken manure on the growth of sweet corn (Zea mays saccharata L.) and assess the antagonism nutrient for K, Ca and Mg in the Inceptisol soil that applied manure, dolomite and fertilizers KCl against growing sweet corn (Zea mays saccharata L.). The result showed the interaction between potassium fertilizer, dolomite and chicken manure on the uptake of calcium, potassium and magnesium in plants sweet corn (Zea mays saccharata L.). There is antagonism nutrient calcium, potassium and magnesium plant sweet corn (Zea mays saccharata L.) on the ground Inceptisol that applied manure, dolomite and fertilizers KCl. The balance of the nutrient uptake of calcium, potassium and magnesium plant achieved at doses of potassium fertilizer at 100 kg K2O / ha